Review of recent progresses on gallium nitride transistor in power conversion application. Issue 1 (2nd January 2020) - Tian, Jiangbo; Lai, Chunyan; Feng, Guodong; Banerjee, Debmalya; Li, Wenlong; Kar, Narayan C.
ABSTRACT: Emerging demands in sustainable energy and power conversion applications are calling for high frequency and high efficiency switching devices. Gallium nitride (GaN) as one type of wide bandgap material has shown its potential in applications where high frequency, high efficiency, and small size are of significance. In this paper, recent progress made toward the development of GaN switching devices is reviewed in the applications of DC to DC, AC to DC, and DC to AC power conversions in terms of power range, efficiency, and switching frequency.